1999
DOI: 10.1111/j.1651-2227.1999.tb00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement haemolytic activity (classical and alternative pathways), C3, C4 and factor B titres in healthy children

Abstract: Ferriani VPL, Barbosa JE, De Carvalho IF. Complement haemolytic activity (classical and alternative pathways), C3, C4 and factor B titres in healthy children. Acta Paediatr 1999; 88: 1062-6. Stockholm. ISSN 0803-5253Values of complement lytic activity of classical and alternative pathways, assessed by measuring the time required to lyse 50% of target red blood cells, and the concentration of complement components C3, C4 and factor B were estimated in the sera of 103 healthy children aged 3 to 14 y. Age-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…While complement components are already synthesized early in fetal life, the complement activity in newborns seems to be lower than in adults ( 54 ). It has been reported that the C1q and properdin levels are low and fB levels are high in children between 1-5 years ( 55 ) and that the concentration of complement proteins C3 and C4 is constant in children under 18 years ( 56 ). The reported generally reduced complement activity may contribute to the higher susceptibility of newborns and infants to invasive infection by various encapsulated bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…While complement components are already synthesized early in fetal life, the complement activity in newborns seems to be lower than in adults ( 54 ). It has been reported that the C1q and properdin levels are low and fB levels are high in children between 1-5 years ( 55 ) and that the concentration of complement proteins C3 and C4 is constant in children under 18 years ( 56 ). The reported generally reduced complement activity may contribute to the higher susceptibility of newborns and infants to invasive infection by various encapsulated bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The lytic complement activity of CP and AP was measured by means of a kinetic assay, as previously described, with minor modifications. 7,8 Briefly, the time required to lyse 50% of an erythrocyte suspension was measured (T1/2). Low T1/2 values for CP and AP correlate with high CP and AP complement activities, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Seroprevalence studies in the United Kingdom (4-7) confirmed a decline in meningococcal disease without a corresponding increase in the proportion of individuals with higher SBA titers. This indicates that alternative mechanisms of protection must be responsible and may include the age-related maturation of the alternative complement pathway (8,9), the presence of bactericidal activity in blood as observed using whole-blood killing assays (10,11), opsonic activity (12), or a combination of these activities. Immunization with a serogroup B outer membrane vesicle (OMV) vaccine, alone or in combination with recombinant antigens, has also been shown to elicit antibodies that have opsonophagocytic killing activity despite SBA titers being Ͻ1:4 (12).…”
mentioning
confidence: 99%